Investigation on designing a fun and interactive learning approach for Database Programming subject according to students' preferences - Rahmalan, Hidayah; Ahmad, Sharifah Sakinah Syed; Affendey, Lilly Suriani (Journal of physics. Conference series, 2020)
Industrial Revolution 4.0 and Internet of Things are two important area which requires development of computational system. To allow this to become reality, students in most higher education institution were taught with programming and database as their fundamental subjects that can be related to develop computational systems and automation concept. For better efficiency, PL/SQL was also being taught but only in a certain higher education institution. In previous years, to attract students being active in learning PL/SQL, we have developed an offline game covering the topic of stored procedure and trigger. To enhance the enjoyable of learning this subject among the students, a survey has been conducted among undergraduate students of the Faculty of Communication and Technology (FICT) in Universiti Teknikal Malaysia Melaka. This survey involved 33 junior students and 12 senior students of Computer Science majoring in Database Management. The results show that students have preferences on a game that include socializing elements such as interaction among themselves, testing their thinking ability with some challenging task and expected elements but should not put pressure on time management.